The Role of Interleukin 12 in Iraqi Patients with Psoriasis - Abbas, Emad A.; Mousa, Hind M (University of Thi-Qar Journal of Science, 2022)
Psoriasis is a chronic skin condition with immune-mediated inflammatory etiology. Many studies have indicated that Interleukin-12 (IL-12) plays an essential role in the severity of psoriasis.So to elucidate IL-12 role in regulating psoriasis promotion, the sera levels of IL-12 are detected in psoriasis patients and healthy people. The study contains 45 individuals with psoriasis, and the same number of healthy persons are included as controls .The PASI (Psoriasis Area and Severity Index) was used to assess the severity of psoriasis. Patients were divided into three groups depending on severity: mild psoriatic patients (13), moderate psoriatic patients(15), and severe psoriatic patients (17).Five ml of serum was obtained from each individual in per groups to determine IL-12 levels. The data demonstrated that the age range (36-45) has the highest prevalence of psoriatic patients (51.11 %). In addition, the female to male ratio in patients with psoriasis was 1.2:1.IL-12 levels in psoriasis patients were significantly higher than in healthy persons (3.55 pg/ml and 2.79 pg/ml). Furthermore, there was a significant association between blood IL-12 levels and PASI for psoriatic patient groups. The findings suggest that IL-12 has a key role in the psoriasis pathogenesis and that it might be utilized to evaluate psoriasis and as a follow-up indicator for those with it.